Rebinding drives cellular retention of small-molecule drugs with abundant targets - Boyan Li; Timothy J. Mitchison (Proceedings of the National Academy of Sciences, 2026)
Many small-molecule antitumor drugs are administered far less frequently than would be predicted from their plasma half-lives, in part because their efficacy is driven by prolonged retention within tumors. Drug retention can be caused by nonspecific protein binding, low membrane permeability, sequestration in acidic compartments, slow target dissociation, and rebinding to empty target sites, but the field has lacked a quantitative framework and preclinical assays for discriminating these mechanisms and predicting retention in vivo. We developed a theoretical framework and a simple two-drug assay for quantifying retention mechanisms in cell-based models. Application to 13 drugs with 8 distinct intracellular targets revealed diverse retention mechanisms. Rebinding emerged as a potent driver of retention whose magnitude was predicted by the target-to-affinity ratio ([Target]/ K d ). Rebinding slows the washout rates of important drugs such as taxanes and rapamycin by 100-fold or more. It also explains the need for high loading concentrations. Our approach bridges a critical gap in pharmacology modeling and provides practical tools to guide the design of intermittent dosing regimens.